(untitled) (Research, Society and Development, 2020)
Facing the challenges to develop more efficient solar dryers, this work used the Computational fluid dynamics (CFD) to test different configurations of lateral air feeding in a fixed bed solar dryer. Through the simulations, it was found the best configuration of air inlet that provided a better fluid-particle contact. It was made a fixed bed solar dryer, which was tested using soybeans seeds and Moringa oleifera LAM leaves to evaluate the drying rate using two bed configurations: fully opened and partially opened inlets. The CFD results indicated that the air flow rate was more pronounced at the bed top, near the exhaust fan. This can explain the poor drying near the bottom for the experiments performed with all lateral inlets opened. According to the simulation results, the air velocity profile was more homogeneous when the air was fed only near the bottom. So, the use of a partially opened configuration led to a more homogenous solar drying, with a drying rate about 300% higher than the one using the fully opened inlets.